(untitled) (Prosiding dan Call Paper Widya Wiwaha, 2024)
In recent years, China’s science and technology have developed rapidly, its economy has become more prosperous, and consumers’ demand for cosmetics has become increasingly high. In order to meet the needs of consumers and the market, traditional marketing and modern marketing have been effectively integrated and promoted. This paper is mainly based on the Pechoin cosmetics industry, focusing on modern marketing and traditional marketing. Data collection methods and data analysis methods are mainly used to analyze and compare modern marketing and traditional marketing in the Pechoin cosmetics industry. At the same time, the competition in the cosmetics market is getting more and more intense. This has further encouraged the world’s leading skin care companies to accelerate their international expansion. Under this condition, if the Pechoin cosmetics industry wants to stand out among the many skin care products, they must implement scientific and effective marketing strategies.